2008
DOI: 10.1089/end.2008.0008
|View full text |Cite
|
Sign up to set email alerts
|

Renal Injury and the Application of Polysaccharide Hemospheres: A Laparoscopic Experimental Model

Abstract: Background and Purpose: Microporous polysaccharide hemospheres (MPH) are hemostatic beads engineered from purified plant starch. MPH accelerates the natural clotting cascade by concentrating clotting factors and proteins on their surface while absorbing aqueous and low molecular weight components from blood. The purpose of this study was to determine the efficacy of MPH in achieving hemostasis in the setting of laparoscopic renal injury. Materials and Methods:In four domestic pigs, 16 laparoscopic renal trocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…Local hemostatic agents are involved in different fields clinically. They are especially used in liver resections, spleen injuries, kidney operations and orthopedic surgery frequently (14)(15)(16)20). For their experimental animal study, Humphrays et al have evaluated the use of MPH in iatrogenic spleen injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Local hemostatic agents are involved in different fields clinically. They are especially used in liver resections, spleen injuries, kidney operations and orthopedic surgery frequently (14)(15)(16)20). For their experimental animal study, Humphrays et al have evaluated the use of MPH in iatrogenic spleen injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Humphreys et al (7,8) have found MPH to be an effective hemostatic agent in studies performed with laparoscopic trocar injuries to the kidney and spleen in pigs. Ersoy et al have reported that MPH is effective in the hemostasis of severe femoral arterial bleeding in rats (5).…”
Section: Mph (Microporous Polysaccharide Hemospheres)mentioning
confidence: 99%
“…4 Among the various classes of hemostatic agents, powdered hemostats have been widely adopted for their easeof-use; however, their efficacy has been limited to low-level bleeds. [5][6][7][8][9][10][11][12][13][14] More recently, the benefit of using powdered hemostats intraoperatively to treat low-level bleeds has been demonstrated clinically. [15][16][17][18][19][20] The two predominant materials within this class of hemostatic agents are a polysaccharide-based powder and a fibrinogen-thrombin based powder.…”
Section: Introductionmentioning
confidence: 99%